Short Communication: The rattans (Arecaceae) of Wallacea - ANDREW HENDERSON; RAMADHANIL PITOPANG (Biodiversitas Journal of Biological Diversity, 2018)
Henderson A, Pitopang R. 2018. Short Communication: The rattans (Arecaceae) of Wallacea. Biodiversitas 19: 18-21. Rattans are spiny, climbing palms whose long, flexible stems provide the canes of commerce. Three rattan genera occur in Wallacea, Calamus, Daemonorops, and Korthalsia. We give a brief review of the geology and biogeography of Wallacea. We follow this with a review of the Wallacean rattan flora in Sulawesi, the Maluku Islands (Moluccas), and Nusa Tenggara. We emphasize how poorly known the rattan flora of Wallacea is. While recent discussions of the rattan flora of the Asian tropics have noted the paucity of species in Wallacea, we consider that the number of species present may be considerably higher.